Reference value of 6-minute walk distance in patients with sub-acute stroke. Issue 5 (3rd July 2020) - Kubo, Hiroki; Nozoe, Masafumi; Kanai, Masashi; Furuichi, Asami; Onishi, Akira; Kajimoto, Kazuki; Mase, Kyoshi; Shimada, Shinichi
ABSTRACT: Background: The 6-minute walk test (6MWT) has strong-to-moderate evidence to assess changes in walking distance for adults with neurologic conditions undergoing rehabilitation. However, the reference value of 6MWT distance according to walking ability and the cutoff value of walking independence in stroke patients in the rehabilitation unit has not been presented. Objectives: To present the reference value of 6MWT distance depending on walking ability and determine the cutoff value of walking independence in stroke patients. Methods: This cross-sectional observational study included 110 stroke patients admitted to the rehabilitation unit within 30 days from stroke onset. 6MWT was used to assess the walking ability at 30 days from stroke onset. Walking ability was classified using the Functional Ambulation Category (FAC). Reference value of 6MWT distance was presented for each walking ability according to FAC score. One-way analysis of variance was computed to investigate 6MWT distance according to walking ability. Receiver operating characteristic curve was used to identify the cutoff value of 6MWT for walking independence. Results: 6MWT distances for each walking ability were as follows: FAC 2 was 141.8 m, FAC 3 was 224.5 m, FAC 4 was 352.6 m, and FAC 5 was 448.8 m ( p < .001). Cutoff value of 6MWT for walking independence was 304 m (area under curve = 0.905, sensitivity of 0.833, specificity of 0.900). Conclusion: 6MWT distance was found to be longer with better walking ability. A distance of 304 m during 6MWT might be useful for judging walking independence in stroke patients.